PENDAMPINGAN DAN PEMBINAAN SARANA PENGOLAHAN USAHA PETERNAKAN KAMBING PE DI DISTRIK AIMAS, KABUPATEN SORONG: Assistance and Training of PE Goat Processing Facilities in Aimas District of Sorong - Muhammad Djunaidi; Trisiwi Widayati; Gino N. Cepeda; Tatak Reko Purwanto; Freddy Pattiselanno (Fakultas Peternakan Universitas Papua, 2022)
ABSTRACT The Ettawah Crossbreed Goat (PE) as a type of small ruminant has several advantages because it is a dual purpose type, which is capable of producing meat and milk. The